Mechanisms of (Fisch.) Bge. var. mongholicus (Bge.) Hsiao (huang qi) and (Oliv.) Diels (dang gui) in Ameliorating Hypoxia and Angiogenesis to Delay Pulmonary Nodule Malignant Transformation - Ying Guo PhD; Peng Yang MS; Zihong Wu PhD; Sanyin Zhang PhD; Fengming You PhD (Integrative Cancer Therapies)
Screening for pulmonary nodules (PN) using low-dose CT has proven effective in reducing lung cancer (LC) mortality. However, current treatments relying on follow-up and surgical excision fail to fully address clinical needs. Pathological angiogenesis plays a pivotal role in supplying oxygen necessary for the progression of PN to LC. The interplay between hypoxia and angiogenesis establishes a vicious cycle, rendering anti-angiogenesis therapy alone insufficient to prevent PN to LC transformation. In traditional Chinese medicine (TCM), PN is referred to as “Feiji,” which is mainly attributed to Qi and blood deficiency, correspondingly, the most commonly prescribed medicines are Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao (huang qi) (AR) and Angelica sinensis (Oliv.) Diels (dang gui) (ARS). Modern pharmacological studies have demonstrated that AR and ARS possess immune-enhancing, anti-tumor, anti-inflammatory, and anti-angiogenic properties. However, the precise mechanisms through which AR and ARS exert anti-angiogenic effects to delay PN progression to LC remain inadequately understood. This review explores the critical roles of hypoxia and angiogenesis in the transition from PN to LC. It emphasizes that, compared to therapies targeting angiogenic growth factors alone, AR, ARS, and their compound-based prescriptions offer additional benefits. These include ameliorating hypoxia by restoring blood composition, enhancing vascular structure, accelerating circulation, promoting vascular normalization, and blocking or inhibiting various pro-angiogenic expressions and receptor interactions. Collectively, these actions inhibit angiogenesis and delay the PN-to-LC transformation. Finally, this review summarizes recent advancements in related research, identifies existing limitations and gaps in knowledge, and proposes potential strategies and recommendations to address these challenges.